Case Report: Reactive Lymphohistiocytic Proliferation in Infant With a Novel Nonsense Variant of IL2RG Who Received BCG Vaccine - Yahya, Amal M.; Al-Hammadi, Suleiman; AlHashaykeh, Nidal O.; Alkaabi, Salwa S.; Elomami, Abdulghani S.; AlMulla, Asia A.; Alremeithi, Majed M.; Kabbary, Rewan M.; Vijayan, Ranjit; Souid, Abdul-Kader (Frontiers in Pediatrics, 2021)
We present here a male young infant with X-linked severe combined immunodeficiency (MIM#300400) due to the novel nonsense variant of IL2RG (interleukin 2 receptor, gamma; MIM#308380), NM_000206.2(IL2RG):c.820_823dup p.Ser275Asnfs*29. He developed aggressive reactive lymphohistiocytic proliferation after receiving the live-attenuated BCG (Bacillus Calmette-Guérin) vaccine at birth. This report advocates for modifying the current practice of early use of BCG. The natural history of his disease also suggests considering IL2RG variants as a potential cause of ‘X-linked recessive Mendelian susceptibility to mycobacterial disease’ (MSMD). His reactive lymphohistiocytic proliferation and massive hepatosplenomegaly simulated hemophagocytic lymphohistiocytosis (HLH, likely triggered by the BCG disease). This entity was masked by the absence of fever and markedly elevated inflammatory biomarkers. Thus, his findings stimulate discussion on the need to modify the diagnostic criteria of HLH, in order to accommodate conditions, such IL2RG variants that block systemic inflammation.